Fluctuation and diversity of Hydromedusae (Hydrozoa, Cnidaria) in a highly productive region of the Gulf of Mexico inferred from high frequency plankton sampling - Sarah Pruski (PeerJ, 2019)
Hydrozoa medusae undergo blooms and seasonal fluctuations; however the drivers of such fluctuations are unknown. To understand how medusa populations fluctuate in response to seasonal factors such as temperature, salinity, dissolved oxygen, and chlorophyll a, and to enhance our taxonomic knowledge of Hydrozoa in Galveston Bay (TX), we performed frequent plankton sampling from September 2015 to September 2016. We collected 1,321 medusae in 190 sampling days. Using molecular barcoding and morphological analyses we identified 25 species, of which 21 are a first record for Galveston Bay and eight for the Gulf of Mexico. Daily medusa abundance is non-linearly related to temperature, with peak abundance estimated with multivariate regression analysis at approximately 21C. The role that temperature plays in driving medusa abundance has implications for future climate change scenarios, given that temperature in the Gulf of Mexico is expected to rise 4 °C by the end of the century. We also show that the biodiversity of the Galveston Bay and the Gulf of Mexico is underestimated and that molecular barcoding is an important and efficient tool to identify large number of medusae. We conclude that dense plankton sampling is necessary to capture both diversity and abundance of planktonic medusae.